Sistem Pengambilan Keputusan Pemilihan Tempat Wisata di Serdang Bedagai Dengan Modifikasi Metode MAUT Dan MOORA - Virgustiawan, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The beauty of tourist attractions is of course one of the main goals of tourists in Serdang Bedagai in spending their holidays and apart from beauty, there are many other things that attract tourists. The increasing number of tourist attractions and different beauties in Serdang Bedagai, as well as the absence of a system that provides information on priority tourist attractions that are really worth visiting, makes it difficult for tourists to determine the best tourist attraction based on the completeness of the facilities and the beauty of the tourism they will visit. they visit. Based on this problem, a decision support system was designed using a combination of Multi Attribute Utility Theory (MAUT) and Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) methods. The results of testing the selection of the best tourist attraction in Serdang Bedagai with the Decision Support System were able to quickly provide decision results for the best tourist attraction in Serdang Bedagai Regency, where with a sample of 5 tourist data it was found that the tourist with the first rank was A4